2020
DOI: 10.1097/gox.0000000000002843
|View full text |Cite
|
Sign up to set email alerts
|

QR678 & QR678 Neo Hair Growth Formulations: A Cellular Toxicity & Animal Efficacy Study

Abstract: Background: Current treatment modalities are limited in their approach and success for hair loss. QR 678 & QR 678 Neo are new formulations, consisting of a combination of growth factors and peptides. This study demonstrates safety analysis of QR 678 & QR 678 Neo formulation, using in vitro cytotoxicity assay and in vivo animal efficacy. Methods: Factors including vascular endothelial growth factor, basic fibroblast growth factor, insulin-like gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…FGF-2 also proved its efficacy in the treatment of oral lichen planus [25] or vitiligo [26]. Animal studies also proved that FGF-2 is promising for regenerative therapy of spinal cord injury [27], of liver injury and liver diseases [28], or for treatment of alopecia [29]. It also enhanced the tendon-to-bone healing in a rabbit model [30].…”
Section: Introductionmentioning
confidence: 95%
“…FGF-2 also proved its efficacy in the treatment of oral lichen planus [25] or vitiligo [26]. Animal studies also proved that FGF-2 is promising for regenerative therapy of spinal cord injury [27], of liver injury and liver diseases [28], or for treatment of alopecia [29]. It also enhanced the tendon-to-bone healing in a rabbit model [30].…”
Section: Introductionmentioning
confidence: 95%
“…26 An animal study was the first to demonstrate safety and effectiveness, and it revealed that they were largely free from negative effects. 27 Additionally, a 1000-patient open-label, prospective, single-arm interventional pilot research using the QR678 Neo® revealed that the formulation of several growth factors in QR678® and QR678 Neo® is equally effective in treating both male and female pattern hair loss. 26 The formulation QR678 Neo® contains hair growth factors, vitamins and minerals, which also have anti-inflammatory action.…”
Section: Introductionmentioning
confidence: 99%
“…16 QR678 Neo ® preparation is a derived from plant source polypeptides and formulated such that biologically replicates the activity of QR678 ® and contains a specific concentration of Sh-polypeptide-9 (bio-mimicking VEGF), Sh-oligopeptide-2 (bio-mimicking IGF-1), Sh-polypeptide-3 (bio-mimicking KGF), Sh-polypeptide-1 (biomimicking bFGF), copper tripeptide, and Sh-oligopeptide-4 (biomimicking thymosin β4) dissolved in a sterilized soluble solution. 17 An animal trial was first conducted to evaluate its safety and efficacy which was found to be over all free from side effects. In addition, an open-label interventional and clinical study was carried out in males using QR678 Neo ® .…”
Section: Introductionmentioning
confidence: 99%
“…QR678 Neo ® preparation is a derived from plant source polypeptides and formulated such that biologically replicates the activity of QR678 ® and contains a specific concentration of Sh‐polypeptide‐9 (bio‐mimicking VEGF), Sh‐oligopeptide‐2 (bio‐mimicking IGF‐1), Sh‐polypeptide‐3 (bio‐mimicking KGF), Sh‐polypeptide‐1 (bio‐mimicking bFGF), copper tripeptide, and Sh‐oligopeptide‐4 (bio‐mimicking thymosin β4) dissolved in a sterilized soluble solution 17 …”
Section: Introductionmentioning
confidence: 99%